2017
DOI: 10.1088/1555-6611/aa8837
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle based saturable absorber for Q-switching in 1.5µm laser application

Abstract: We demonstrate passive Q-switching in an erbium-doped fiber laser (EDFL) cavity using gold nanoparticles as a saturable absorber (SA) for the first time. By using a thermal deposition method, gold with nanosized particles was plated onto polyvinyl alcohol film to form the SA. The SA was incorporated into a laser cavity, sandwiched between two fiber ferrules. The EDFL generates a Q-switching pulse in the 1560 nm region with a tunable repetition rate from 24.34 kHz to 88.11 kHz. The pulse tuned to a maximum inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…For instance, Muhammad et al demonstrated Q‐switched EDFL by using copper nanoparticles as SA 22 . In another work, Ahmad et al reported Q‐switched pulse generation using gold nanoparticles (GNP) obtained through thermal deposition method whereby maximum pulse width of 4.25 μs was realized 23 . Both reported works 22,23 are carried out in a 1.55 µm region based on an erbium‐doped fiber laser (EDFL) cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Muhammad et al demonstrated Q‐switched EDFL by using copper nanoparticles as SA 22 . In another work, Ahmad et al reported Q‐switched pulse generation using gold nanoparticles (GNP) obtained through thermal deposition method whereby maximum pulse width of 4.25 μs was realized 23 . Both reported works 22,23 are carried out in a 1.55 µm region based on an erbium‐doped fiber laser (EDFL) cavity.…”
Section: Introductionmentioning
confidence: 99%
“…22 In another work, Ahmad et al reported Q-switched pulse generation using gold nanoparticles (GNP) obtained through thermal deposition method whereby maximum pulse width of 4.25 μs was realized. 23 Both reported works 22,23 are carried out in a 1.55 µm region based on an erbium-doped fiber laser (EDFL) cavity. Recently, pulse generation in a 3 μm mid-infrared region has also attracted increased attention.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Muhammad et al demonstrated Q-switched erbium-doped fiber laser (EDFL) by using copper nanoparticles as saturable absorbers [19]. In another work, Ahmad et al reported Q-switched pulse generation using gold nanoparticles obtained through thermal deposition method whereby maximum pulse width of 4.25 µs was realized [20]. All the reported works are carried out in 1.55 µm region based on the EDFLcavity.…”
Section: Introductionmentioning
confidence: 99%
“…23 Gold nanoparticles (GNPs) represent a widely used and typical metal nanoparticle that has been widely studied in the past few years. [24][25][26] By measuring the nonlinear optical response using the Z-scan technique, 24 GNPs have been identified as a highly suitable candidate as SAs because of their applicability in the case of the SPR effect. In the case of GNPs, their third-order nonlinear coefficient has been determined to be as high as ∼10 −6 , which is higher than that of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Used as an SA, GNPs have been successfully introduced into the fiber laser cavity in order to achieve pulse operation as expected. 25,26 Recently reported progress 25,26 has meant that GNPs have attracted significant attention and are a promising candidate for enhancement of optical nonlinear effects, which means that they clearly have a potentially important role to play within the general application fields of nonlinear optics. However, to date the authors of this article are unaware of any reported work relating to multiwavelength pulse generation with GNPs used as an SA incorporated within the fiber laser cavity.…”
Section: Introductionmentioning
confidence: 99%